Oxysterols Protect Epithelial Cells Against Pore-Forming Toxins - Ormsby, Thomas J. R.; Owens, Sian E.; Clement, Liam; Mills, Tom J.; Cronin, James G.; Bromfield, John J.; Sheldon, Iain Martin (Frontiers in Immunology, 2022)
Many species of bacteria produce toxins such as cholesterol-dependent cytolysins that form pores in cell membranes. Membrane pores facilitate infection by releasing nutrients, delivering virulence factors, and causing lytic cell damage - cytolysis. Oxysterols are oxidized forms of cholesterol that regulate cellular cholesterol and alter immune responses to bacteria. Whether oxysterols also influence the protection of cells against pore-forming toxins is unresolved. Here we tested the hypothesis that oxysterols stimulate the intrinsic protection of epithelial cells against damage caused by cholesterol-dependent cytolysins. We treated epithelial cells with oxysterols and then challenged them with the cholesterol-dependent cytolysin, pyolysin. Treating HeLa cells with 27-hydroxycholesterol, 25-hydroxycholesterol, 7α-hydroxycholesterol, or 7β-hydroxycholesterol reduced pyolysin-induced leakage of lactate dehydrogenase and reduced pyolysin-induced cytolysis. Specifically, treatment with 10 ng/ml 27-hydroxycholesterol for 24 h reduced pyolysin-induced lactate dehydrogenase leakage by 88%, and reduced cytolysis from 74% to 1%. Treating HeLa cells with 27-hydroxycholesterol also reduced pyolysin-induced leakage of potassium ions, prevented mitogen-activated protein kinase cell stress responses, and limited alterations in the cytoskeleton. Furthermore, 27-hydroxycholesterol reduced pyolysin-induced damage in lung and liver epithelial cells, and protected against the cytolysins streptolysin O and Staphylococcus aureus α-hemolysin. Although oxysterols regulate cellular cholesterol by activating liver X receptors, cytoprotection did not depend on liver X receptors or changes in total cellular cholesterol. However, oxysterol cytoprotection was partially dependent on acetyl-CoA acetyltransferase reducing accessible cholesterol in cell membranes. Collectively, these findings imply that oxysterols stimulate the intrinsic protection of epithelial cells against pore-forming toxins and may help protect tissues against pathogenic bacteria.